2018
DOI: 10.4103/jfo.jfds_36_17
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of time since death based on light microscopic, electron microscopic, and electrolyte analysis in the gingival tissue

Abstract: Background:Estimation of time since death is an important parameter in forensic science. Although there are various methods available, precise estimation is still to be established.Aim:The present study aimed to evaluate the histological and ultrastructural changes in the gingival tissue along with the changes in electrolyte levels (sodium, potassium, calcium, and magnesium) among the three groups which included normal, 2, and 4 h since death.Materials and Methods:For light microscopic examination and electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…15 In comparison, other researchers have compared antemortem and post-mortem mucosal samples to determine post-mortem cellular changes. 7,8,10,16 Three studies have been conducted to associate changes in salivary gland oral mucosa with time since death. 11,12,20 Based on evaluations of the cellular changes in antemortem and post-mortem mucosa, Gururaj suggested that the decomposition process begins in the initial 24 hours, while Pradeep et al concluded that the decomposition process at the cellular level begins within 10 hours of death.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15 In comparison, other researchers have compared antemortem and post-mortem mucosal samples to determine post-mortem cellular changes. 7,8,10,16 Three studies have been conducted to associate changes in salivary gland oral mucosa with time since death. 11,12,20 Based on evaluations of the cellular changes in antemortem and post-mortem mucosa, Gururaj suggested that the decomposition process begins in the initial 24 hours, while Pradeep et al concluded that the decomposition process at the cellular level begins within 10 hours of death.…”
Section: Discussionmentioning
confidence: 99%
“…8 In a recent study, Muthukrishnan et al described early and late postmortem changes in five antemortem and five postmortem gingival samples. 10 Due to sample size limitations, none of the aforementioned studies were able to provide statistical confirmation of the usefulness of light microscopic cellular changes in the oral mucosa as a method of predicting time since death. [9][10][11]15,20,21 Moreover, several studies either evaluated post-mortem cellular changes in the gingiva alone or in the labial mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La evaluación de tejidos provenientes de la cavidad oral para estimación del IPM se focalizó en 3 estudios detectados en esta revisión, aplicando métodos IHQs en mucosa labial (Charan Gowda et al) y tejido gingival (Fais et al; Mazzotti et al). Eso se suma a la tendencia iniciada años antes con propuestas de evaluaciones de cambios histológicos para estimar el IPM en esos mismos tejidos (Pradeep et al, 2009;Yadav et al, 2012;; Mahalakshmi et al, 2016;Muthukrishnan et al, 2018). Yavad et al (2015), afirman que existe mucha información publicada respecto a los fenómenos postmortem en tejidos orales, lo que podría restringir el rol de los médicos forenses al momento de estimar el IPM.…”
Section: Discussionunclassified